Survival following Multimodality Treatment Including Surgery for Stage IA–IIIB Small-Cell Lung Cancer - Weckler, Barbara Christine; Baldes, Natalie; Schirren, Joachim (The Thoracic and Cardiovascular Surgeon, 2019)
Background Prognosis in limited disease small-cell lung cancer (SCLC) after concurrent chemoradiotherapy is poor. While some studies show better survival after multimodality treatment including surgery, other trials failed to prove a surgery-related survival benefit. Therefore, this study investigated survival in stage IA–IIIB SCLC following surgery combined with chemotherapy and/or thoracic radiotherapy.Methods We retrospectively reviewed all stage IA–IIIB SCLC patients without supraclavicular lymph node involvement at a single institution between January 1999 and August 2016 after multimodality treatment with curative intent. This comprised surgery consisting of primary tumor resection and systematic lymph node dissection combined with chemotherapy, chemoradiotherapy, or thoracic radiotherapy. Survival was determined using the Kaplan–Meier method, and differences were compared using log-rank tests. The risk of locoregional relapse was calculated.Results A total of 47 patients (29 men, 18 women; mean age: 62 years) were included. Thirty-day mortality was 0%. Overall median survival was 56 months, and 2-, 3-, 5-, and 10-year survival rates were 69, 54, 46, and 30%, respectively. The only significant prognostic factor (p = 0.006) was R0 resection (n = 40) increasing median survival to 64 versus 17 months in case of technical inoperability (n = 5). The risk of locoregional relapse was 2.5% (n = 1) after R0 resection.Conclusions Multimodality treatment including surgery was safe and led to considerable survival. R0 resection was the only factor extending survival. It could be achieved in most patients and was associated with a low risk of locoregional relapse. Prospective randomized controlled studies are needed to define best practice in stage IA–IIIB SCLC.
Keywords: limited disease small-cell lung cancer; multimodality treatment for small-cell lung cancer; lung cancer treatment (surgery; medical)